Implementasi Manajemen Kurikulum dalam Meningkatkan Mutu Lulusan Santri Madrasah Diniyah Miftahul Ulum Al Yasini Pasuruan - Diana Nadhifah; Wahidmurni; Indah Aminatuz Zuhriyah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research examines the implementation of curriculum management in improving the quality of Islamic boarding school graduates at Madrasah Diniyah Miftahul Ulum Al-Yasini Pasuruan. The aim of the research is to describe in depth the process of planning, implementing and evaluating the curriculum to improve the quality of santri graduates. This research uses a descriptive qualitative approach to understand curriculum management at Madrasah Diniyah Miftahul Ulum Al-Yasini. The focus is on exploring the phenomenon of religious education, involving data collection through interviews, observation and documentation. The research results show that curriculum planning in this madrasa includes five main components: needs analysis, holistic curriculum objectives, relevant teaching materials, varied learning methods, and ongoing evaluation. With a systematic approach, madrasas strive to produce students who not only have in-depth religious knowledge, but also practical skills and good character, so they are ready to face challenges in society. In the implementation process, active learning approaches, teacher involvement, and adapting the curriculum to local contexts have succeeded in improving the quality of graduates. Collaboration-based projects also strengthen students' social and adaptive skills. Curriculum evaluation is carried out through surveys, interviews and observations to collect in-depth data regarding the achievement of student competencies. Evaluation results are used as a basis for continuous improvement, ensuring the curriculum remains relevant to the demands of the times. This systematic evaluation has had a positive impact on the students' readiness to contribute to society. By implementing comprehensive and collaborative curriculum management, Madrasah Diniyah Miftahul Ulum Al-Yasini has succeeded in producing graduates who are qualified, adaptive, and ready to contribute positively in social and professional life.